Development of a method to quantify total and free irinotecan and 7-ethyl-10-hydroxycamptothecin (SN-38) for pharmacokinetic and bio-distribution studies after administration of irinotecan liposomal formulation - Wenqian Yang; Zimeng Yang; Jieru Liu; Dan Liu; Yongjun Wang (Elsevier, 2019)
In 2015, liposomal formulation of irinotecan (ONIVYDE) has been approved by FDA and widely applied in the treatment of pancreatic cancer. ONIVYDE is a novel liposome formulation, entrapping CPT-11 in the aqueous core of vesicles using a modified gradient loading method. Due to toxicity concerns, it is essential to explore a rapid and reliable method to effectively isolate and quantify the non-liposomal, namely, free CPT-11and total CPT-11 in plasma. This study focuses on separation of non-liposomal CPT-11, evaluation of the pharmacokinetics of free CPT-11 and total CPT-11 and bio-distribution after intravenous administration of CPT-11 liposome. Free CPT-11 in plasma was separated by solid-phase extraction (SPE). The amount of total CPT-11 and main metabolite 7-ethyl-10-hydroxycamptothecin (SN-38) in plasma was quantified by ultra-performance liquid chromatography-MS/MS. The calibration curves fitted well and lower limit of quantitation for SN-38, free CPT-11, total CPT-11 and CPT-11 in tissue and were 5 ng/ml, 10 ng/ml, 4.44 ng/ml and 25 ng/ml respectively. The recoveries, precision and accuracy of the method appear satisfactory. Using this method, the pharmacokinetics and bio-distribution of CPT-11 liposome formulation after an intravenous dose of 2.5 mg/kg were then investigated. Keywords: Irinotecan, Liposome, UPLC-MS-MS, SPE, Pharmacokinetics, Bio-distribution